Core Principles and Global Practices of Deposit Insurance Scheme: A Comparison of the Trend with the Nepalese System - Bhatta, Kiran Prasad (Banking Journal, 2012)
DOI: http://dx.doi.org/10.3126/bj.v2i1.5705 Banking Journal 2012; 2(1): 59-83